2016
DOI: 10.1371/journal.pone.0162545
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of Geometric Accuracy of MRI Protocols Used in Experimental Stroke

Abstract: It has recently been suggested that multicenter preclinical stroke studies should be carried out to improve translation from bench to bedside, but the accuracy of magnetic resonance imaging (MRI) scanners routinely used in experimental stroke has not yet been evaluated. We aimed to assess and compare geometric accuracy of preclinical scanners and examine the longitudinal stability of one scanner using a simple quality assurance (QA) protocol. Six 7 Tesla animal scanners across six different preclinical imaging… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Despite the multitude of advances in imaging-guided therapies, there is still a strong need to further improve the quality of research to obtain predictive and clinically translatable data. To this end, research activities should involve collaborative community efforts, including multi-center studies as suggested 10 , 194 and applied recently 54 , 195 - 198 . The concept of reverse-translating quality standards from clinical studies into preclinical work has shown promise and overall acceptance to further enhance translatability of research 199 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the multitude of advances in imaging-guided therapies, there is still a strong need to further improve the quality of research to obtain predictive and clinically translatable data. To this end, research activities should involve collaborative community efforts, including multi-center studies as suggested 10 , 194 and applied recently 54 , 195 - 198 . The concept of reverse-translating quality standards from clinical studies into preclinical work has shown promise and overall acceptance to further enhance translatability of research 199 .…”
Section: Discussionmentioning
confidence: 99%
“…Since we only recently became aware of the problem of non-whole brain coverage for MLC, sham animals were scanned using our old standard protocol with 20 slices covering mid- and forebrain only. 27 In plane directions are termed x (lateral) and y (ventral-dorsal), whereas slice selection direction z is referring to the caudal-rostral axis.…”
Section: Methodsmentioning
confidence: 99%
“…When computing the loss, we interpret the samples in the batch as a whole sample and calculate the dice loss over all voxels in the cluster. The dice loss formulation used here is proposed by Fabian et al, which is adapted from the multi-class adaptation of the variant proposed by M.Drozdzal et al [23] The implementation of dice loss is as follows: [23] The ISLES 2018 Challenge tackled the segmentation of stroke lesion core from acute CT scan. Imaging data from acute stroke patients in two centers is presented within 8 hours of stroke onset.…”
Section: Loss Functionmentioning
confidence: 99%